Accuracy of triage strategies for human papillomavirus DNA-positive women in low-resource settings: A cross-sectional study in China - Wang, Margaret (Chin J Cancer Res, 2017)
OBJECTIVE: CareHPV is a human papillomavirus (HPV) DNA test for low-resource settings (LRS). This study assesses optimum triage strategies for careHPV-positive women in LRS. METHODS: A total of 2,530 Chinese women were concurrently screened for cervical cancer with visual inspection with acetic acid (VIA), liquid-based cytology and HPV testing by physician- and self-collected careHPV, and physician-collected Hybrid Capture 2 (HC2). Screen-positive women were referred to colposcopy with biopsy and endocervical curettage as necessary. HPV-positivity was defined as ≥1.0 relative light units/cutoff (RLU/CO) for both careHPV and HC2. Primary physician-HC2, physician-careHPV and self-careHPV and in sequential screening with cytology, VIA, or increased HPV test-positivity performance, stratified by age, were assessed for cervical intraepithelial neoplasia (CIN) grade 2/3 or worse (CIN2/3+) detection. RESULTS: The sensitivities and specificities of primary HPV testing for CIN2+ were: 83.8%, 88.1% for physician-careHPV; 72.1%, 88.2% for self-careHPV; and 97.1%, 86.0% for HC2. Physician-careHPV test-positive women with VIA triage had a sensitivity of 30.9% for CIN2+ versus 80.9% with cytology triage. Self-careHPV test-positive women with VIA triage was 26.5% versus 66.2% with cytology triage. The sensitivity of HC2 test-positive women with VIA triage was 38.2% versus 92.6% with cytology triage. The sensitivity of physician-careHPV testing for CIN2+ decreased from 83.8% at ≥1.0 RLU/CO to 72.1% at ≥10.00 RLU/CO, while the sensitivity of self-careHPV testing decreased from 72.1% at ≥1.0 RLU/CO to 32.4% at ≥10.00 RLU/CO; similar trends were seen with age-stratification. CONCLUSIONS: VIA and cytology triage improved specificity for CIN2/3 than no triage. Sensitivity with VIA triage was unsuitable for a mass-screening program. VIA provider training might improve this strategy. Cytology triage could be feasible where a high-quality cytology program exists. Triage of HPV test-positive women by increased test positivity cutoff adds another LRS triage option.